Relationship between anatomical characteristics of pulmonary veins and atrial fibrillation recurrence after radiofrequency catheter ablation: a systematic review and meta-analysis - Qi, Dan; Zhang, Jianjun (Frontiers in Cardiovascular Medicine, 2023)
Background: The aim of the current study was to investigate the potential relationship between anatomical characteristics of pulmonary veins (PVs) and atrial fibrillation recurrence (AFR) following radiofrequency catheter ablation (RFCA), specifically focusing on PV diameter and cross-sectional orifices index (CSOA). The analysis was based on a comprehensive review of currently available literature, providing valuable insights for the prevention and treatment of AFR. Methods: Data was collected from five databases, including PubMed, MEDLINE, EMBASE, and Cochrane, spanning the period from 2004 to October 2022.The search strategy utilized Medical Subject Headings (MeSH) terms related to PV diameter, PV size, PV anatomy, and AFR. Indicators of PV diameter and CSOA from the included studies were collected and analyzed, with Weight mean difference (WMD) and 95% confidence intervals (CIs) representing continuous variables. Results: The meta-analysis included six studies. The results revealed that patients with AFR had a significant larger mean PV diameter compared to those without AFR (MD 0.33; 95%CI 0.01, 0.66; P=0.04; I2=33.80%). In a meta-analysis of two studies involving a total of 715 participants, we compared the diameters of the left upper pulmonary vein (LSPV), left lower pulmonary vein (LIPV), right upper pulmonary vein (RSPV), and right lower pulmonary vein (RIPV) between patients with AFR and patients without AFR. The results showed that there were nostatistically significant differences between the two groups in any of the four data items (all P>0.05). Additionally, the pooled estimate revealed that LSPV-CSOA, LIPV-COSA, RSPV-COSA, and RIPV-CSOA were greater in the AFR group compared to the non-AFR group, but the differences were not statistically significant (all P>0.05). Conclusion: We found evidence supporting the notion that the PV diameter of patients who experienced AFR after RFCA was significantly larger than that of patients without AFR. The findings suggested that the PV diameter could serve as a potential predictor of the risk of AFR following RFCA.